Investigating EFL Learners’ Perceptions and Practices Using the Indonesia's Prepaid Mobile Application Ruangguru - Saiful Marhaban; Ika Apriani Fata (AT-TA'LIM, 2025)
Ruangguru, one of Indonesia's prepaid applications, has facilitated autonomous learning for students. Ruangguru (henceforth RG) is a mobile application enhances online learning organizations by aligning it with Indonesia's curriculum. RG offered students a platform with distinctive characteristics to support online study in several subjects. The present study examines students' viewpoints on using Ruangguru, one of Indonesia's online learning prepaid platforms, and ascertains its advantages and disadvantages. The current study employed a qualitative methodology, utilizing interviews to collect data. The participants comprised senior high school students from several cities in Indonesia who were enrolled in regular classes, subscribed to RG, and willingly provided their consent by signing a consent form. The findings revealed that RG possesses several benefits, including the ability to set one's own pace, user-friendliness, independent learning, and a flexible platform. It allowed pupils to learn without any limitations on time or location. However, the RG was unable to substitute regular classes with the presence of teachers, the decrease of social interactions in learning, the significant disparity between the wealthy and the impoverished, and the diminishing role of teachers. Ruangguru's primary focus is students' academic achievement. Yet, it is crucial to resolve other notable aspects, such as inadequate feedback, teacher guidance, and lack of peer interaction. As a further recommendation, to evaluate the effectiveness of the RG, it is also recommended that students' achievement and the impact of using RG in the EFL classroom be analyzed and cross-referenced.